2019
DOI: 10.1002/lary.27933
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measuring social attention of thyroid neck scars and transoral surgery using eye tracking

Abstract: Objective Measure the social attention of thyroid neck scars and transoral surgery using eye tracking. Methods Observers viewed images of patients with thyroid neck scars, control patients with no scars, and patients who underwent transoral thyroidectomy as an eye‐tracking monitor recorded their eye movements. Hotelling's multivariate analysis, followed by planned posthypothesis testing, were used to compare fixation times for the central triangle (CT), peripheral face, and neck between the three groups. To as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 33 publications
1
54
0
2
Order By: Relevance
“…Neck scarring, a major concern after thyroidectomy, is related to quality of life, irrespective of the severity and length of the scar . Therefore, it is reasonable to avoid a visible neck scar if it can be done safely and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Neck scarring, a major concern after thyroidectomy, is related to quality of life, irrespective of the severity and length of the scar . Therefore, it is reasonable to avoid a visible neck scar if it can be done safely and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Casual observers in their study spent significantly more time looking at the necks of open thyroidectomy patients and less time on the peripheral face (the area outside of the central triangle of the eyes, nose, and mouth). 12 The current study builds on this pilot and earlier literature by exploring whether TOETVA/TOEPVA can prevent the attentional distraction caused by a neck scar following open surgery. We utilized a series of 60 patient photos of various racial identities.…”
Section: Discussionmentioning
confidence: 98%
“…Previous pilot work using eye-tracking technology has shown that open thyroidectomy scars cause attentional bias to the neck compared to transoral thyroidectomy in a handful of patients, suggesting that neck scars are proximal and noticeable enough to alter the conserved visual processing patterns of human faces. 12 The current study builds upon earlier work by employing eye-tracking methodology to look at a large cohort of patients who either underwent open neck surgery (thyroidectomy, parathyroidectomy, or thyroidectomy with concomitant neck dissection) or their transoral endoscopic counterparts (TOETVA or transoral endoscopic parathyroidectomy via a vestibular approach [TOEPVA]). This group of patients included those who presented at various times for follow-up (ie, weeks to months) and were of different racial identities.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients find this troubling and seek other options to minimize the scar. [2][3][4][5] Richmon et al in a cadaver, 6,7 demonstrated the feasibility of a transoral vestibular technique. It was brought to clinical practice in 2014 8 with the endoscopic approach and was reported to be safe and effective in a larger series of patients in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been the standard approach for more than 100 years, it does leave a permanent cervical scar that may heal in a variable fashion. Some patients find this troubling and seek other options to minimize the scar …”
Section: Introductionmentioning
confidence: 99%